Colloidal droplet desiccation on a electrowetting-on-dielectric (EWOD) platform - Ghosh U.U.; Dhara T.; Bakshi J.; Nath K.; DasGupta S. (My University, 2025)
The physics of the effects of electric field on the desiccation of colloidal droplets, comprising of dispersed negatively charged nanoparticles [2 μl, 1(w/w. %)], are studied in a standard electrowetting-on-a-dielectric configuration. The extent of contact line pinning during evaporation is found to be a function of the magnitude of the applied voltage and quantified in terms of the dimensionless electrowetting number (η). The pinned contact line led to higher particle compaction as evidenced by the characterization of dried colloidal film thicknesses. Crack formation and their dynamics have been analyzed in detail to elicit the interplay of forces near the contact line region and on the compaction front. These aspects of crack formation are elucidated in the light of magnitude and polarity of the applied electric field. It is found to influence the crack front initiation velocity, the geometry, the number of cracks, and an attempt is made to explain the same via first principle-based approaches. Therefore, this study indicates the possibility of using electrowetting as a technique to fine-tune the crack formation behavior in thin colloidal films. © 2024 Author(s).